Implementasi Sistem Manajemen Hotspot Berbasis Mikrotik untuk Optimalisasi Akses Internet di Pesantren - Anshori, Anshori; Rifa’i, M. Ali (Journal of Computer Science and Information System(JCoInS), 2025)
This study aims to examine the implementation of a Mikrotik-based hotspot management system to optimize internet access at Pondok Pesantren An-Nur, Ogan Komering Ilir, South Sumatra. The central issue addressed is the limited and uneven internet management within a boarding school environment. A qualitative case study approach was employed to explore both the technical and social dimensions of the system's implementation. Data were collected through semi-structured interviews, participatory observations, and document analysis, involving informants such as the network administrator, teachers, boarding school administrators, and active students. Data analysis revealed three main themes: (1) the design of a Mikrotik RB750-based network system with centralized authentication and proportional bandwidth allocation; (2) users’ perceptions and responses to access control and connection stability; and (3) the digital cultural transformation within the pesantren resulting from structured technological regulation. The findings indicate that the system not only improves network performance but also promotes digital discipline and content supervision in alignment with pesantren values. This research contributes to the understanding of technology integration in value-based educational institutions and proposes a practical, efficient, and contextual network management model. The practical implications are relevant for pesantren managers and policymakers in digital education. Further research is recommended to explore similar implementations across different religious institutions using a comparative approach.